"Apply to Muslims What Was Said of the Jews:" Popes and Canonists Between a Taxonomy of Otherness and Infidelitas. (6th February 2014) - Stantchev, Stefan K.
<x content-type="archive" xml:space="preserve">Abstract</x> This article analyzes the targets of papal policies on Christians' relations with non-(Roman)Christians contained in canon law's On Jews, Saracens, and Their Servants in a historical period that has attracted comparatively little attention: the mid-thirteenth to the late fifteenth century. It argues the inherent ambiguity of the normative discourse on "proper" relations with "infidels." On the one hand, popes and canonists faithfully preserved a taxonomy of otherness inherited from the church's ancient past. On the other hand, they often reduced all difference to the pastoral distinction between flock and "infidels." The conflation of non-Christians occurred in multiple ways: through the explicit extension of a specific policy's targets, overt canonistic discussion, the tacit application of the law to analogous situations, or its simplification for use in the confessional. As a result, a number of policies aimed originally at a specific target were applied to all non-Christians. In the course of the later Middle Ages, a whole group of policies meant to define Christians' proper relations with others became potentially applicable against all non-Christians. In the words of a widely, if regionally disseminated, penitential work, all that was said of the Jews applies to the Muslims and all that was said of heretics, applies to schismatics.